2008
DOI: 10.1074/jbc.m802396200
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation Modifies Protein Kinase C δ-dependent Phosphorylation of Cardiac Troponin I

Abstract: PKC␦ leads to depressed maximum tension and cross-bridge kinetics, attributable to a dominant effect of cTnI-Thr144 phosphorylation. Our data implicate PKC␦-Tyr 311 /Thr 505 phosphorylation as dynamically regulated modifications that alter PKC␦ enzymology and allow for stimulus-specific control of cardiac mechanics during growth factor stimulation and oxidative stress. Protein kinase C␦ (PKC␦)2 is a ubiquitous serine/threonine kinase implicated in a wide range of cellular responses (1, 2). PKC␦ is conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
86
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 29 publications
3
86
1
Order By: Relevance
“…Cantrell and colleagues have also recently shown that deletion of PDK-1 in thymocytes does not abolish PKC A-loop phosphorylation [132], while the enzyme has also been reported to autophosphorylate its own A-loop in cardiomyocytes via a mechanism that is dependent on prior tyrosine phosphorylation of the enzyme at the hinge domain by Src kinases [46,32]. These studies imply that autophosphorylation or indeed a kinase other than PDK-1 may catalyse phosphorylation at this site on PKC .…”
Section: Accepted M Manuscriptmentioning
confidence: 96%
See 3 more Smart Citations
“…Cantrell and colleagues have also recently shown that deletion of PDK-1 in thymocytes does not abolish PKC A-loop phosphorylation [132], while the enzyme has also been reported to autophosphorylate its own A-loop in cardiomyocytes via a mechanism that is dependent on prior tyrosine phosphorylation of the enzyme at the hinge domain by Src kinases [46,32]. These studies imply that autophosphorylation or indeed a kinase other than PDK-1 may catalyse phosphorylation at this site on PKC .…”
Section: Accepted M Manuscriptmentioning
confidence: 96%
“…Phosphorylation of PKC at Tyr-313 by Src family kinases has also been reported in a variety of cell types in response to non-apoptotic stimuli [117][118][119]46,120,32,121,100]. While some of these studies have shown that phosphorylation at Tyr-313 is required for PKC function, one consequence of Tyr-313 phosphorylation is that it regulates the ability of the enzyme to autophosphorylate its own A-loop and thus fine-tune substrate specificity [32,46].…”
Section: Accepted M Manuscriptmentioning
confidence: 97%
See 2 more Smart Citations
“…Serines 23 and 24, which are located in the cardiac specific N-terminal domain (residues 1-30) of cTnI (absent in skeletal TnI) are the main targets of PKA (Kooij et al 2010b;Solaro 2008). It has recently became evident that these sites can also be cross-phosphorylated by PKCδ, PKCα, PKCβ, PKG, and PKD (Table 1) (Haworth et al 2004;Layland et al 2002Layland et al , 2005Swiderek et al 1990;Sumandea et al 2008). It has been generally accepted that phosphorylation of these sites is an important mechanism for increasing the rate of relaxation during β-adrenergic receptor stimulation in the heart.…”
Section: Thin Filament Regulationmentioning
confidence: 99%